Peptides in energy balance and obesity [ - Fruhbeck, Gema (Frontiers in nutritional science, 2009)
Obesity is one of the relevant public health concerns and it is evident that body weight control is achieved through highly integrated physiological interactions like nutrient selection. Presenting an account of the roles of specific peptides in energy alance, this title provides an understanding of the patho-physiology of energy balance.